The Social Technique for Creating the Future - Faragó, László (Discussion Papers, 2012)
The present discussion paper is a cross section or a thematic summary of a consid¬erably longer work. The author attempts to offer a sound theoretical foundation for planners in the critical era between the development of a new planning system and the abandonment of the former ‘socialist’ type planning in the early 1990s. A general theory can not only lead to a better understanding of the gist and possible forms of planning but can also serve as a basis for a con¬tinuously developing methodology of learning and rationalization. In an attempt to foster changes in attitudes to planning, the author’s desire is to develop a new philosophy of plan-ning with emphasis on teleology. Whilst raising awareness of the limitations we encounter in the exploration of a given situation, his aim is to replace fal¬lacies about the unknown reality with desirable and accepted visions. The author depicts planning as a cyclical process of rationalization containing monitoring and learning cycles, a continuous experimentation where theory and practice are collated with each other whose ultimate result will be manifested in the acquisition of new a posterirori knowledge. The paper does not contain the traditional presentation or description of theories developed by other experts. References to empirical works or case studies are also missing in spite of the 25 years’ experience of the author as a planner. The approach of empirical sociology, i.e. the description of events occurring in a given context is also deliberately rejected, the author applies a post-positive approach instead. If he has revived and re-interpreted ideas and taken over - or vulgarised for the sake of practical work - time-honoured arguments, this was in order to use them as components of ‘some kind of planning theory’.